2002
DOI: 10.1161/01.str.0000030109.12281.23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Thrombolysis on MRI Parameters and Functional Outcome in Acute Stroke <6 Hours

Abstract: Background and Purpose-The goals of this study were to examine MRI baseline characteristics of patients with acute ischemic stroke (AIS) and to study the influence of intravenous tissue plasminogen activator (tPA) on MR parameters and functional outcome using a multicenter approach. Methods-In this open-label, nonrandomized study of AIS patients with suspected anterior circulation stroke, subjects received a multiparametric stroke MRI protocol (diffusion-and perfusion-weighted imaging and MR angiography) withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
210
0
23

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(246 citation statements)
references
References 53 publications
13
210
0
23
Order By: Relevance
“…This also illustrates the dynamic nature of the core-penumbra. Because several studies have reported that ischemic lesions were undetected with DWI 29,30 or that severe reductions in ADC normalized over time depending on the duration and severity of ischemia, 31 it is likely that serial measurements may be needed to improve MRI sensitivity to better estimate tissue injury. Recent reviews report existence of 'mini-core' and 'mini-penumbra' (interdigitation) and their spatiotemporal dynamics in IHC, 2 which HRS could detect noninvasively from MRI ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…This also illustrates the dynamic nature of the core-penumbra. Because several studies have reported that ischemic lesions were undetected with DWI 29,30 or that severe reductions in ADC normalized over time depending on the duration and severity of ischemia, 31 it is likely that serial measurements may be needed to improve MRI sensitivity to better estimate tissue injury. Recent reviews report existence of 'mini-core' and 'mini-penumbra' (interdigitation) and their spatiotemporal dynamics in IHC, 2 which HRS could detect noninvasively from MRI ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, major reperfusion and lesser infarct growth predicted better neurological outcome after stroke (41). Thus, a major predictor for recovery is early effective reperfusion (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…However, a few groups have observed changes in the fMRI response, which correlate with the clinical literature. Stimulation of the impaired limbs produced activation in the intact sensorimotor cortex, and formerly unresponsive regions in the peri-infarcted tissue (Abo et al, 2001;Dijkhuizen et al, 2001;Rother et al, 2002). Interestingly, when repetitive fMRI sessions were performed in the same animals, three types of responders were characterized: those that retained, those that lost, and those that exhibited only a transient loss of the bloodoxygen-level-dependent response that was independent of infarct size measurements (Weber et al, 2008).…”
Section: Functional Mrimentioning
confidence: 99%